Au rendez-vous allemand (1) - Agnès Bouvier (Flaubert: Revue Critique et Génétique, 2010)
How can you translate or transpose one world into another and make it believable?  Flaubert’s solution for Salammbô was to adopt the point of view of Antiquity.  Going back to Antiquity’s speeches and tales, from and with the Classics and our knowledge of them, he chose a sympathetic stance.  This attitude is in line with contemporary admonitions of the “new” critical and historical school that came from Germany where Herder’s thought, passed on by Renan, had a central role.  Herder’s History of Hebrew Poetry, published in 1783, was translated in 1845.  It is a seminal text of German criticism in that it approaches the sacred text in an exclusively textual dimension.  Even the title of his book is an invitation to consider the Bible from the point of view of art, that is, for its effects.  According to Herder, biblical exegesis must performed by shifting the critical angle to develop in the modern reader an esthetic sensibility similar to that of the original reader.